Sustainable Financial Management of MSMEs in Disadvantaged Regions through Digitalization Post-Pandemic - Annida Salsabila, Nayla; Puspitasari, Diana (Inovasi Analisis Data, 2025)
Purpose: To explore the effect of digital financial capabilities on sustainable financial performance via digital financial inclusion. Method: A quantitative survey-based study using structural equation modeling for analyzing MSME digital and financial management practices. Findings: Results show the importance of digital financial inclusion as a key driver in the relationship between digital financial capabilities and sustainable financial performance. DFL, fintech use, and digital record keeping improve the inclusiveness that in turn increases financial sustainability. Liquidity discipline: its direct impact on overall performance. The former demonstrates the extent to which sustainable cash flow management processes directly contribute to overall performance. Nevertheless, digital readiness fully enhances not all of the digital finance-performance relationships in every context, also demonstrating that technological preparedness is inadequate to improve financial performance but need complementing with effective financial governance. Novelty: This research presents a comprehensive accounting-based sustainability framework incorporating digital financial inclusion as a mediating mechanism and digital readiness as a contextual factor. It pushes beyond the efficiency outcomes that have dominated digital finance research to focus on the scope and implications of long-term financial accountability and resilience. Implications: The results provide insights for MSME managers, policy makers, and financial service providers in designing an inclusive digital finance intervention focusing on developing the financial discipline, capability, and sustainable performance instead of immediate digital adoption itself.